Assessing Authentic Representation of Learning Outcomes in Tests of Teacher Education - Nishat Zafar ,Sher Zaman, (PJE, 2023)
Instructional decisions depend principally on the results of assessment in any of the education systems. But for the purpose, authentic representation i.e., direct alignment between the predetermined learning objectives and assessment tasks of the instructional system is essential. However, the weak linkage of the given two factors in instruction, makes ‘validity of results’ as well as resultant certification, questionable. The current study was, therefore, conducted to address the issue of alignment in learning objectives and tests, for assessing authentic representation of learning outcomes in tests being used for appraisal of teacher education.